Troilus and Cressida notes - Lowers, James K. (Lincoln, Nebraska Cliffs Notes, 1964)
Study aid, including introduction, scene-by-scene synopses with comments and summaries, character analyses, and question and answer section.
"Including introduction to the play, the prologue,summaries and commentaries, character analyses, selected bibliography."
Keywords: Shakespeare, William -- 1564-1616.